Improving the safety of fresh meat - Sofos, John Nikolaos (Woodhead Publishing in food science and technology., 2005)
It is widely recognised that food safety depends on effective intervention at all stages in the food chain, including the production of raw materials. This book provides an authoritative reference summarising the wealth of research on reducing microbial and other hazards in raw and fresh red meat.